A core human gut microbe, Mediterraneibacter gnavus, produces a broad-spectrum bacteriocin mediterrocin - Gabrielle Mingolelli; Jessia Raherisoanjato; Duong Trinh; Yu Gao; Matthew Henke (mBio)
ABSTRACT A diverse, stable community of microbes in the human gut is strongly tied to health. The factors that regulate microbial community structure and dynamics are ill-defined. In this study, we discover mediterrocin, a bacteriocin produced by the core member of the human gut microbiota, Mediterraneibacter gnavus (previously Ruminococcus gnavus). Following a screen for antimicrobial production by clinical isolates of M. gnavus, mediterrocin was isolated by bioactivity-guided fractionation from strain RJX1121, identified by mass spectrometry, and confirmed by gene disruption. Mediterrocin, an 89 amino acid secreted protein, is a broad-spectrum bacteriocin. Annotation of the mediterrocin biosynthetic gene cluster revealed a wide distribution among Bacillota (previously Firmicutes), including the M. gnavus type strain ATCC249149. The type strain of M. gnavus also produces mediterrocin, but in lower titers than RJX1121 under our culture conditions. Mediterrocin is inhibitory to multiple M. gnavus strains, but with varying sensitivity, with isolates from patients with inflammatory bowel disease displaying the greatest susceptibility. Beyond M. gnavus, mediterrocin demonstrated inhibitory activity against other Lachnospiraceae and the gram-negative pathogen Morganella morganii. Further characterization of mediterrocin may clarify how this core member of the healthy microbiome interacts with other community members and how the relative abundance of M. gnavus changes in microbiome dysbiosis associated with several diseases.IMPORTANCEMediterraneibacter gnavus is a core member of the gut microbiome and implicated in several diseases. Direct competition between M. gnavus and other members of the microbiome may contribute to the shift from a diverse, structured community to dysbiosis observed in disease. Identifying molecular mechanisms of microbial competition will aid future studies of these disease-relevant bacteria and clarify how community structure is maintained. We report the discovery of mediterrocin, a bacteriocin present in many species in the orders Lachnospirales and Eubacteriales, but clade-specific within M. gnavus. Mediterrocin, produced by health-associated strains of M. gnavus, inhibits the growth of disease-associated M. gnavus strains and a broad spectrum of gut commensal bacteria and pathogens.